A Systematic Review of the Impact of Side Frictions on Road Service Levels in Urban Roadways - Pratama, Angga; Kharisma, Galuh; Setiawan, Teguh Puji; Rijaluddin, Arief; Taufik, Mohamad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study presents a systematic literature review (SLR) on the impact of side frictions on the level of service (LOS) in urban roadways. Side frictions, which include pedestrian activity, on-street parking, street vendors, and loading/unloading activities, are often underestimated in traditional traffic models. However, they significantly reduce road capacity and disrupt smooth traffic flow, especially in densely populated urban environments. This review analyzes 56 peer-reviewed studies published between 2020 and 2025, focusing on indicators used to assess side friction effects, such as vehicle delay, lane occupancy, flow rate, and speed. The study also highlights the classification of side friction by intensity level and the growing use of modeling tools like VISSIM, SIDRA, Synchro, and GIS integration in quantifying their impacts. Visualizations generated through VOSviewer provide insights into keyword co-occurrence and research trends. Findings show that simulation-based analysis not only helps evaluate current conditions but also supports the testing of mitigation strategies. The study concludes that incorporating side frictions into roadway performance analysis is essential for more accurate, context-sensitive urban transport planning and policy development.